PAUD RELIGIOUS VALUES-BASED CURRICULUM MANAGEMENT - Wahidah, Finadatul; Rahman, Kholilur; Intaningtyas, Alfiyatin (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2022)
In educational process, curriculum management must be implemented to ensure that curriculum planning, implementation, and evaluation occur effectively and efficiently. This study focuses on Pre-Kindergarten Education Institutions (PAUD), an educational service program offered by formal and informal a variety of educational groups, which is targeted particularly at young children in order to promote their physical and psychological development. This study aimed to explore the curriculum management based on religious values used in Raudatul Athfal Miftahul Ulum Terpadu Suren Jember as well as its planning, implementation, and evaluation. The result of the study showed: (1) the planning of curriculum management based on religious values at RA Miftahul Terpadu Suren includes Hablum minallah such as carrying out the dhuha prayer, reciting AL-Qur’an etc; Hablum minannas such as speaking politely, behaving well, and greeting to others; Hablum minannafsi such as having a sense of self-love, Hablum minal alam such as caring to the environment. These planning processes are the outcome of previous evaluations. (2) At this school, the implementation of religious values-based curriculum consists of two levels, namely school level and grade level. (3) Evaluation of religious values-based curriculum management entails both process and outcome evaluation.